Financial Well Being: Suatu Tinjauan Sistematis dan Bibliometrik - Abel Tasman; Rahmi Fahmy; Hafiz Rahman; Ma'ruf Ma'ruf; Rida Rahim (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
Financial Well Being is an interesting phenomenon being studied by researchers in various countries. This study describes Financial Well Being (FWB) in two perspectives, namely dimensions (forming factors) and antecedents (influencing factors). This study uses a Systematic Literature Review (SLR) and Bibliometric approach with the PRISMA and Vos Viewer methods. The research period is 5 years in the 2017-2022. The articles used were articles published by the three main publishers namely Elsevier, Emerald and Wiley as well as the Scopus database. Articles were analyzed based on research focus, research methods, research geography, and variable clusters used. The conclusions are (1) studies that determine the antecedent of FWB are more dominant than studies that determine the dimensions of FWB, (2) the research geography of developed and developing countries is in a balanced position, meaning that research on FWB is research that has been extensively researched by both, (3) variable financial capability, conscientiousness, personality traits, and practice are the most suitable variables for future research.